2000
DOI: 10.1046/j.1462-2920.2000.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of abundant sulphate‐reducing bacteria in marine oxic sediment layers by a combined cultivation and molecular approach

Abstract: The depth distribution and diversity of sulphate-reducing bacteria (SRB) was analysed in the upper intertidal zone of a sandy marine sediment of the Dutch island Schiermonnikoog. The upper centimetre of the sediment included the oxic-anoxic interface and was cut into five slices. With each slice, most probable number (MPN) dilution series were set up in microtitre plates using five different substrates. In the deeper sediment layers, up to 1 x 10(8) cm(-3) lactate-utilizing SRB were counted, corresponding to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 55 publications
2
41
1
Order By: Relevance
“…Total cell numbers in surface sediments at the Heincke Seep, Gullfaks, were high with 6.7×10 9 and 7.9×10 9 single cells ml −1 sediment in the uppermost 10 cm at station 771 and 766, respectively (Table 4). These cell numbers are higher than previously reported for nonseep sandy sediments in the North Sea (0.2-3.0×10 9 cells; Llobet-Brossa et al, 1998;Wieringa et al, 2000;Rusch et al, 2001Rusch et al, , 2003 and underline the stimulating effect of methane seepage on the density of the microbial community inhabiting sands. The only other published cell counts from The tree was calculated on a subset of nearly full-length sequences by maximum-likelihood analysis in combination with filters, which considered only 50% conserved regions of the 16S rRNA of δ-proteobacteria to exclude the influence of highly variable positions.…”
Section: Microbial Diversity and Community Composition Based On 16s Rmentioning
confidence: 49%
“…Total cell numbers in surface sediments at the Heincke Seep, Gullfaks, were high with 6.7×10 9 and 7.9×10 9 single cells ml −1 sediment in the uppermost 10 cm at station 771 and 766, respectively (Table 4). These cell numbers are higher than previously reported for nonseep sandy sediments in the North Sea (0.2-3.0×10 9 cells; Llobet-Brossa et al, 1998;Wieringa et al, 2000;Rusch et al, 2001Rusch et al, , 2003 and underline the stimulating effect of methane seepage on the density of the microbial community inhabiting sands. The only other published cell counts from The tree was calculated on a subset of nearly full-length sequences by maximum-likelihood analysis in combination with filters, which considered only 50% conserved regions of the 16S rRNA of δ-proteobacteria to exclude the influence of highly variable positions.…”
Section: Microbial Diversity and Community Composition Based On 16s Rmentioning
confidence: 49%
“…This renders the typical black horizons in the deeper permanent anoxic layers of the mat (van Gemerden, 1993). The most important group of SRB is related to Desulfomicrobiaceae, members of which have been isolated from nearby locations (Wieringa et al, 2000). We did not found sequences belonging to this group in ST2, which might suggest a preference for low-salinity environments.…”
Section: Functional Diversitymentioning
confidence: 68%
“…and Desulfomicrobium sp. (Stal et al, 1985;de Wit and van Gemerden, 1988;Visscher et al, 1992;Wieringa et al, 2000). DNA sequence analysis of a 16S rRNA gene clone library revealed mainly Cyanobacteria, Proteobacteria and Bacteriodetes species .…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis of isolates (Devereux et al 1990) and the introduction of 16S rRNA based molecular tools (Amann et al 1995) now allow SRB to be identified and quantified in their natural habitat. This type of investigation was only recently applied to marine sediments (Devereux et al 1996, Llobet-Brossa et al 1998, Ravenschlag et al 1999, Bowman et al 2000, Wieringa et al 2000.…”
Section: Somentioning
confidence: 99%